Evaluating occupational health and safety service quality by SERVQUAL: a field survey study - Demir, Pelin; Gul, Muhammet; Guneri, Ali Fuat (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
The adverse impact of occupational accidents and occupational diseases on the society have recently increased a lot since the industrial-oriented society is getting more and more widespread. Although attempts regarding occupational health and safety (OHS) increase in Turkey, they are still at an inadequate level. OHS experts prepare employees for a healthy and safer working environment, so that work accidents can be eliminated and employees can be healthy psychologically and physically. At the same time, the worksites can be prevented from being financially damaged and productivity can be improved. The aim of this study is to measure OHS service quality by the evaluations of OHS experts from various sectors and workplaces. In this way, the OHS performance is measured, the difference between perceptions and expectations of the OHS experts is determined and deficiencies are revealed. In the study, the OHS activities are examined in five dimensions using the SERVQUAL scale; tangibility, reliability, responsiveness, assurance and empathy. The questionnaire is carried out using a Likert-type five-point scale among 81 OHS experts from different sectors. In conclusion, SERVQUAL analysis is introduced as a useful tool for employers to better understand what they need to know about OHS services.
Keywords: occupational health and safety; SERVQUAL; service quality; experts; questionnaire; Business & Economics